New compacton and solitary pattern solutions of the nonlinear modified dispersive Klein-Gordon equations - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2007)
The special exact solutions of the modified nonlinearly Klein-Gordon-type equations mKG(m, n, k) are investigated by using some ansatze. Thus, we obtain new soliton solutions with compact support and solitary pattern solutions having infinite slopes or cusps, solitary wave and periodic solutions are obtained. The properties of the mKG(m,n,k) equations are shown in some figures. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: De Vries Equation; N) Equations; K) Equations; Families; Solitons; Waves; Support; K(M